A Validated RP-HPLC Method for the Estimation of Quetiapine in Bulk and Pharmaceutical Formulations - D. Suneetha; A. Lakshmana Rao (E-Journal of Chemistry, 2010)
A new, simple, specific, sensitive, rapid, accurate and precise RP-HPLC method was developed for the estimation of quetiapine in bulk and pharmaceutical formulations. Quetiapine was chromatographed on a reverse phase C18 Waters column (75x4.6 mm I.D., particle size 3.5 μm) in a mobile phase consisting of phosphate buffer (pH 3.0 adjusted with orthophosphoric acid) and acetonitrile in the ratio 40:60 v/v. The mobile phase was pumped at a flow rate of 0.8 mL/min with detection at 291 nm. The detector response was linear in the concentration of 20-120 μg/mL. The limit of detection and limit of quantitation was found to be 0.2 and 0.75 μg/mL, respectively. The intra and inter day variation was found to be less than 1%. The mean recovery of the drug from the solution was 99%. The proposed method is simple, fast, accurate, precise and reproducible hence, it can be applied for routine quality control analysis of quetiapine in bulk and pharmaceutical formulations.